New material of Chelus Colombiana (Testudines; Pleurodira) from the Lower Miocene of Colombia (2010)
In this article, we describe newly discovered lower Miocene shell material of Chelus colombiana from central Colombia that represents the geologically oldest, unequivocal record for the genus and we re-interpret the specific affinities of upper Miocene Chelus material previously reported (Bocquentin, 1988; Bocquentin and Rodrigues dos Santos, 1989) from Estado do Acre, Brazil. We also document the pattern and distribution of iliac, pubic, ischial, axillary, and inguinal scars among all three Chelus species. We argue that those features are useful for differentiating Chelus species and we incorporate them into the first cladistic analysis of intra-generic relationships for the genus.